Biological control of the banana aphid for sustainable management of banana bunchy top disease in sub-Saharan Africa. IITA-USAID Linkage Program Final Technical Report; IITA project report - Messing, R.; Hanna, R.; Kumar, P. Lava (International Institute of Tropical Agriculture, 2010)
This report presents the summary of the findings of a project on development of sustainable biological options for the control of banana aphid (Pentalonia nigronervosa) to reduce the incidence and spread of banana bunchy top virus (BBTV) and enhance banana/plantain productivity in BBTV-affected countries in sub-Saharan Africa. This specific project has the following objectives, (i) develop and refine rearing methods of the newly discovered species, Endaphis fugitiva, further to establish viable laboratory colonies that can be used experimentally and also shipped to Africa; and (ii ) Identify and introduce candidate natural enemies from the area of origin of the banana aphid into quarantine in Hawaii for testing and eventual introduction into Africa. Newly emerged Endaphis fugitiva adults were released in the cage. Several weeks later, leaf samples were examined microscopically and Endaphis-parasitized aphids were observed. This is the first successful rearing of a complete generation of the parasitoid in captivity. However, parasitism rate of the aphid colonies was quite low. Parasitized Pentalonia aphids were not detected during the extensive surveys towards the end of rainy season of 2010 in three islands of Indonesia. The project has given an opportunity to both IITA and its collaborating partners to enhance the technical capacity at their respective institutions in matters of biological control research. The project, through its foreign exploration component, has established new links with scientific counterparts in Indonesia and New Guinea - where foreign exploration were conducted jointly, which will also enhance their capacity in matters of searching for and testing biological control agents.